Does Transient Opioid Use Increase Risk of Short-Term Respiratory Exacerbation among Older Adults with Chronic Obstructive Pulmonary Disease?. (2nd November 2021) - Ramachandran, Sujith; Rong, Yiran; Bhattacharya, Kaustuv; Salkar, Monika; McGwin, Gerald; Yang, Yi; Bentley, John P.
Abstract: The objective of this study was to examine the association between transient opioid use and acute respiratory exacerbations among older Medicare beneficiaries with COPD. This study was conducted using national Medicare 5% sample administrative claims data between 2012 and 2016 and employed a case-crossover design. The date of eligible COPD exacerbation events was defined as the index date and the presence of opioid prescriptions during a 7-day exposure window prior to index date was compared to a set of 10 control periods, each 7-days long. The association between opioid exposure and COPD exacerbation was estimated using a conditional logistic regression with robust sandwich estimators, after accounting for known time-varying confounders. Among 16, 290 eligible COPD exacerbations included in the study sample, the average patient age was 77.08 years, and 64.2% of events occurred in women. Transient exposure to opioids was associated with a 76% increase in the odds of an acute COPD exacerbation (OR: 1.76, 95%CI: 1.67–1.84), and each 25 mg increase in morphine milligram equivalent dose was associated with a 18% increase in the odds of exacerbation (OR: 1.18, 95% CI: 1.15–1.21). Effect estimates were consistent across subgroup analyses conducted among events identified in the emergency department versus hospital, and among individuals with a single exacerbation event versus those with multiple exacerbations. Transient exposure to opioids was associated with an increased short-term risk of respiratory exacerbation among older adults with COPD. Treatment decisions for breathlessness among individuals with COPD need to account for the benefit-risk profile of opioids. Supplemental data for this article is available online at https://doi.org/10.1080/15412555.2021.2013460 .